A justiça de Tamar: estudo exegético de Gênesis 38 - Suzuki, Francisca Cirlena Cunha Oliveira (2023)
This doctoral thesis investigates the poetic narrative in Genesis 38. It is composed of thirty verses written, originally, in Hebrew. It is in this language that the episode is read and studied. The story of Tamar is narrated to say that she was chosen by Judah, the third son of Jacob, she is, firstly, Er’s wife who firstborn of Judah. After her first husband’s death, she is given as a wife to Onã, the second son of Judah. Widowed again, her father-in-law does not permit her marriage to Shelah, his third son, so he sends her back to her father’s house. Tamar, however, insists on belonging to Judah’s family. Tamar with her face covered by a veil waits for her father-in-law in the path. He saw her and considered her a prostitute, in this encounter generated two children. When Tamar proves the paternity of her children, amid what appeared to be a scandal of major proportions,so he recognizes how much her daughter-in-law “wasfair” (הָקְ דָצ.( Therefore, the story in Gen 38 apparently narrates a model of behavior and/or a moral proposal. Thus, the protagonist character, that is, Tamar, invites the listener-reader to identify themselves with her, instead of rejecting her. However, to make this decision, it is urgent to carry out a detailed and accurate reading. This is the intention of this doctoral thesis which is attentive to the literary context of the book of Genesis, the Pentateuch, and the Hebrew Bible, it aims to study the poetic configuration of the narrative in Gen 38 and the thematic details contained therein. For example, the veil, a piece of clothing, having its connotations observed, does present Tamar as a prostitute or as a bride? In this case, the parallels in the Bible seem to contradict certain popular understandings that only mirror certain prejudices. Finally, by putting together the various observations in relation to chapter 38 in the book of Genesis, the thesis established here is that Tamar, as a family woman, represents an important female model of justice, deserving of gaining social relevance